Early referring saved lives in kidney transplant recipients with COVID-19: a beneficial role of telemedicine - Zahradka, Ivan; Petr, Vojtech; Jakubov, Katarina; Modos, Istvan; Hruby, Filip; Viklicky, Ondrej (Frontiers in Medicine, 2023)
There is a strong impetus for the use of telemedicine for boosting early detection rates and enabling early treatment and remote monitoring of COVID-19 cases, particularly in chronically ill patients such as kidney transplant recipients (KTRs). However, data regarding the effectiveness of this practice are lacking. In this retrospective, observational study with prospective data gathering we analyzed the outcomes of all confirmed COVID-19 cases (n=955) in KTRs followed at our center between March 1, 2020, and April 30, 2022. Risk factors of COVID-19 related mortality were analyzed with focus on the role of early referral to the transplant center, which enabled early initiation of treatment and remote outpatient management. This proactive approach was dependent on the establishment and use of a telemedicine system, which facilitated patient-physician communication and expedited diagnostics and treatment. The main exposure evaluated was early referral of KTRs to the transplantation center after confirmed or suspected COVID-19 infection. The primary outcome was the association of early referral to the transplantation center with the risk of death within 30 days following a COVID-19 diagnosis, evaluated by logistic regression. We found that KTRs who referred their illness to the transplant center late had a higher 30-day mortality (4.5 vs. 13.6%, p < 0.001). 30-day mortality after the diagnosis of COVID-19 was independently associated with late referral to the transplant center (OR 2.08, 95% CI 1.08 – 3.98, p = 0.027), higher age (OR 1.09, 95% CI 1.05 – 1.13, p < 0.001), higher body mass index (OR 1.06, 95% CI 1.01 – 1.12, p = 0.03), and lower eGFR (OR 0.96, 95% CI 0.94 – 0.98, p < 0.001) in multivariable logistic regression. Furthermore, KTRs who contacted the transplant center late were older, had longer time from transplantation, lived farther from the center and presented with higher Charlson Comorbidity Index. In conclusion, a well-organized telemedicine program can help to protect KTRs during an infectious disease outbreak by facilitating pro-active management and close surveillance. Furthermore, these results can be extrapolated to other vulnerable populations, such as patients with chronic kidney disease, diabetes or autoimmune diseases requiring the use of immunosuppression.